Pemberian Jintan Hitam (Nigella Sativa L) dan Madu (Apis Mellifera) Sebagai Suplemen Zat Besi dalam meningkatkan Kadar Hemoglobin Ibu Hamil - Nurhayati Nurhayati (MPI Press, 2022)
Introduction: Iron deficiency anemia is one of the most common disorders during pregnancy. Pregnant women generally experience a decrease in iron so only a small amount of iron in the fetus is needed for normal iron metabolism. During pregnancy, the indication of anemia is if the HB concentration is less than 11 g% in the first and third trimesters and the HB level is less than 10.5 g% in the second trimester Objectives: The purpose of this study was to determine the effect of giving nigella sativa oil and honey on hemoglobin levels of pregnant women at PMB Rosminta Siregar Bojong Gede in 2022 Method: This study used a quasi-experimental design using one group pre-test and post-test methods. The number of samples is 30 pregnant women. The research instrument used observation sheets and statistical tests using the dependent t-test. Result: The results showed that there was a significant difference in hemoglobin levels of pregnant women before and after giving Nigella Sativa and Honey with a 2-tailed sign of 0.000. It can be seen that the 2-tailed sign is 0.000 < (0.05). Conclusion: The study concluded that there were differences in the administration of nigella sativa oil and honey on the hemoglobin levels of pregnant women at PMB Rosminta Siregar Bojong Gede in 2022.